KARAKTERISTIK SIFAT OPTIK NANOPARTIKEL KARBON (CARBON DOTS) DENGAN METODE UV-VIS DRS (ULTRAVIOLET-VISIBLE DIFFUSE REFLECTANCE SPECTROSCOPY) - Jumardin; Akhiruddin Maddu; Koekoeh Santoso; Isnaeni (JFT : Jurnal Fisika dan Terapannya, 2022)
Research on the synthesis of Carbon Dots using the laser ablation method has been carried out at a time duration of 1, 2, and 3 hours (energy 60 mJ, wavelength 1064 nm and frequency 10 Hz). This research uses organic material from Tea and Toluene as the carbon solvent. The characterization method uses a UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS) spectrum to measure the reflectance value and uses the Kubelka-Munk equation to determine the relationship between the absorbance coefficient parameter (s) and the scattering reflectance coefficient (k). The size and morphological characterization methods used Particle Size Analyzer (PSA) and Transmission Electron Microscopy, while the functional group characteristics used the Fourier Transform InfraRed (FTIR) tool. FTIR spectra show the O-H group which is a hydroxyl bond and N-H is a carboxylic acid. The results of measurement and analysis of bandgap energy at different time durations for direct transition (n=2) were 1 hour (3.62 eV, 342.49 nm), 2 hours (3.24 eV, 380.61 nm) and 3 hours (2.74, 451.82 nm). Indirect transitions (n=1/2) were 1 hour (3.17 eV, 391.02 nm), 2 hours (2.50 eV, 495.36 nm) and 3 hours (2.21 eV, 559.04).